台灣地區2005至2008年創傷性脊髓損傷之流行病學研究 - 莊美芳; Chuang，Mei- Fang (2010)
表目錄.i 圖目錄.ii 第一章 緒論.1 第一節、研究背景及動機.1 第二節、研究目的.3 第三節、名詞定義.4 第二章 文獻探討.7 第一節、創傷性脊髓損傷之定義.7 第二節、創傷性脊髓損傷發生率與死亡率探討.8 第三節、創傷性脊髓損傷之年齡與性別探討.11 第四節、創傷性脊髓損傷之損傷原因探討.13 第五節、創傷性脊髓損傷之脊髓損傷部位及障礙型態.15 第三章 材料與方法.17 第一節、研究對象.17 第二節、資料分析.18 第三節、統計分析.19 第四章、研究結果.20 第一節、創傷性脊髓損傷發生率及基本人口學資料分佈情形.21 第二節、創傷性脊髓損傷患者受傷原因探討.23 第三節、創傷性脊髓損傷患者受傷情形分佈.24 第四節、創傷性脊髓損傷患者神經障礙程度分佈以及住院天數 分析.26 第五節、創傷性脊髓損傷患者受傷結果分析.28 第六節、各危險因子與病患出院時神經障礙程度之相關性.31 第五章、討論.33 第六章、研究限制.38 第七章、結論與建議.39 參考文獻.40 附表.46 附圖.52 附件.76 表目錄 表2-2-1、各國創傷性脊髓損傷之發生率.46 表2-2-2、各國創傷性脊髓損傷之死亡率.47 表2-3、各國創傷性脊髓損傷患者之平均年齡與性別比. .48 表2-4、各國創傷性脊髓損傷患者之受傷原因. .49 表2-5、各國創傷性脊髓損傷患者之受傷部位及神經障礙程度之比例.50 表3-1-1、合作醫院列表.51 表3-1-2、脊髓損傷ICD-9項目.52 表4-1、976位脊髓損傷患者基本人口學特性與受傷原因.53 表4-2、性別、年齡與受傷原因之分佈.57 表4-3-1、受傷情形之分佈.59 表4-3-2、性別、年齡、受傷原因與受傷部位之分佈.62 表4-4-1、受傷部位與脊髓神經障礙種類之分佈.64 表4-4-2、住院天數之分佈.65 表4-4-3、脊髓神經障礙種類與加護病房住院天數之分佈.67 表4-5-1、受傷結果.68 表4-5-2、性別、年齡、受傷原因、受傷部位、脊髓神經障礙種類與受傷結果之分佈.70 表4-5-3、性別、年齡、受傷原因、受傷部位、脊髓神經障礙種類與受傷結果(死亡與植物人)之分析.74 表4-6、影響脊髓神經障礙之危險因子. .75 圖目錄 圖4-1-1 受傷年份分佈.54 圖4-1-2 年齡分佈.54 圖4-1-3 性別分佈.55 圖4-1-4戶籍地分佈.55 圖4-1-5 受傷原因分佈.56 圖4-1-6 受傷者所乘座之車型.56 圖4-2-1 性別與受傷原因.58 圖4-2-2 年齡與受傷原因.58 圖4-3-1 受傷部位分佈.60 圖4-3-2 合併傷害部位分佈.60 圖4-3-3脊髓神經障礙種類分佈.61 圖4-3-2-1 性別與受傷部位.62 圖4-3-2-2年齡與受傷部位.63 圖4-3-2-3 受傷原因與受傷部位.63 圖4-4-1 受傷部位與脊髓神經障礙種類.64 圖4-4-2-1 加護病房和普通病房的平均住院天數.65 圖4-4-2-2加護病房住院天數分佈.66 圖4-4-2-3普通病房住院天數.66 圖4-4-3-1脊髓神經障礙種類與加護病房住院天數.67 圖4-5-1-1受傷結果.68 圖4-5-1-2死亡原因.69 圖4-5-1-3 受傷後醫學合併症.69 圖4-5-2-1 性別與受傷結果.71 圖4-5-2-2 年齡與受傷結果.71 圖4-5-2-3受傷原因與受傷結果.72 圖4-5-2-4 受傷部位與受傷結果.72 圖4-5-2-5脊髓神經障礙種類與受傷結果. .73 1. Institute of Occupational Safety and Health. http://www.iosh.gov.tw/data/f2/sp42-1.htm. Accessed December 10, 2008. 2. Center NSCIS. Spinal cord injury Facts and figures at a glance. J Spinal Cord Med. 2008;31(3):357-358. 3. Centers for Disease Control and Prevention.Spinal Cord Injury (SCI): Fact Sheet. http://www.cdc.gov/ncipc/factsheets/scifacts.htm. Accessed December 6, 2008 4. French DD, Campbell RR, Sabharwal S, Nelson AL, Palacios PA, Gavin-Dreschnack D. Health care costs for patients with chronic spinal cord injury in the Veterans Health Administration. J Spinal Cord Med. 2007;30(5):477-481. 5. The Potential Development Center for Spinal Cord. http://www.scsrc.org.tw/index.php. Accessed December 6, 2008. 6.Samsa GP, Patrick CH, Feussner JR. Long-term survival of veterans with traumatic spinal cord injury. Arch Neurol 1993;50:909-14 7. Chen HY, Chiu WT, Chen SS, et al. A nationwide epidemiological study of spinal cord injuries in Taiwan from July 1992 to June 1996. Neurol Res. Dec 1997;19(6):617-622. 8.Griffin MR,O’Fallon WM, Opitz JL, Kurland LT. Mortality,survival and prevalence: traumatic spinal cord injury in Olmsted County, Minnesota,1935-1981. J Chronic Dis 1985;38:643-53. 9. Pajareya K. Traumatic spinal cord injuries in Thailand: an epidemiologic study in Siriraj Hospital, 1989-1994. Spinal Cord. Oct 1996;34(10):608-610. 10. Griffin MR, Opitz JL, Kurland LT, Ebersold MJ, O'Fallon WM. Traumatic spinal cord injury in Olmsted County, Minnesota, 1935-1981. Am J Epidemiol. Jun 1985;121(6):884-895. 11. Lan C, Lai JS, Chang KH, Jean YC, Lien IN. Traumatic spinal cord injuries in the rural region of Taiwan: an epidemiological study in Hualien county, 1986-1990. Paraplegia. Jun 1993;31(6):398-403. 12. Pickett GE, Campos-Benitez M, Keller JL, Duggal N. Epidemiology of traumatic spinal cord injury in Canada. Spine. Apr 1 2006;31(7):799-805. 13. Albert T, Ravaud JF. Rehabilitation of spinal cord injury in France: a nationwide multicentre study of incidence and regional disparities. Spinal Cord. Jun 2005;43(6):357-365. 14. Biering-Sorensen E, Pedersen V, Clausen S. Epidemiology of spinal cord lesions in Denmark. Paraplegia. Feb 1990;28(2):105-118. 15. Garcia-Reneses J, Herruzo-Cabrera R, Martinez-Moreno M. Epidemiological study of spinal cord injury in Spain 1984–1985. Paraplegia. 1990;28(3). 16. Knutsdottir S. Spinal cord injuries in Iceland 1973-1989. A follow up study. Paraplegia. Jan 1993;31(1):68-72. 17. Soopramanien A. Epidemiology of spinal injuries in Romania. Paraplegia. Nov 1994;32(11):715-722. 18. Martins F, Freitas F, Martins L, Dartigues JF, Barat M. Spinal cord injuries--epidemiology in Portugal's central region. Spinal Cord. Aug 1998;36(8):574-578. 19. Silberstein B, Rabinovich S. Epidemiology of spinal cord injuries in Novosibirsk, Russia. Paraplegia. Jun 1995;33(6):322-325. 20. Frankel HL, Coll JR, Charlifue SW, et al. Long-term survival in spinal cord injury: a fifty year investigation. Spinal Cord. Apr 1998;36(4):266-274. 21. Maharaj JC. Epidemiology of spinal cord paralysis in Fiji: 1985-1994. Spinal Cord. Sep 1996;34(9):549-559. 22. O'Connor P. Incidence and patterns of spinal cord injury in Australia. Accid Anal Prev. Jul 2002;34(4):405-415. 23. Shingu H, Ohama M, Ikata T, Katoh S, Akatsu T. A nationwide epidemiological survey of spinal cord injuries in Japan from January 1990 to December 1992. Paraplegia. Apr 1995;33(4):183-188. 24. Otom AS, Doughan AM, Kawar JS, Hattar EZ. Traumatic spinal cord injuries in Jordan--an epidemiological study. Spinal Cord. Apr 1997;35(4):253-255. 25. Karacan I, Koyuncu H, Pekel O, et al. Traumatic spinal cord injuries in Turkey: a nation-wide epidemiological study. Spinal Cord. Nov 2000;38(11):697-701. 26. Kraus JF, Franti CE, Riggins RS, Richards D, Borhani NO. Incidence of traumatic spinal cord lesions. J Chronic Dis. Oct 1975;28(9):471-492. 27. Sekhon LH, Fehlings MG. Epidemiology, demographics, and pathophysiology of acute spinal cord injury. Spine. Dec 15 2001;26(24 Suppl):S2-12. 28 Wyndaele M, Wyndaele JJ. Incidence, prevalence and epidemiology of spinal cord injury: what learns a worldwide literature survey? Spinal Cord. Sep 2006;44(9):523-529. 29. Gur A, Kemaloglu MS, Cevik R, et al. Characteristics of traumatic spinal cord injuries in south-eastern Anatolia, Turkey: a comparative approach to 10 years' experience. Int J Rehabil Res. Mar 2005;28(1):57-62. 30. Burney RE, Maio RF, Maynard F, Karunas R. Incidence, characteristics, and outcome of spinal cord injury at trauma centers in North America. Arch Surg. May 1993;128(5):596-599. 31. Hoque MF, Grangeon C, Reed K. Spinal cord lesions in Bangladesh: an epidemiological study 1994 - 1995. Spinal Cord. Dec 1999;37(12):858-861. 32.Saunders LL,Selassie AW,HILL EG,et al.Traumatic spinal cord injury mortality,1981-1998. J Traumatic2009;66;184-90. 33.DeVivo MJ,Stover SL,Black kj.Prognostic factors for 12-year survival after spinal cord injury.Arch Phys Med Rehabil 1992;73;156-62 34.Spinal cord injury.Facts and figures at a glance.J Spinal Cord Med 2005;28;379-80 35. da Paz AC, Beraldo PS, Almeida MC, Neves EG, Alves CM, Khan P. Traumatic injury to the spinal cord. Prevalence in Brazilian hospitals. Paraplegia. Sep 1992;30(9):636-640. 36. Aung TS, el Masry WS. Audit of a British Centre for spinal injury. Spinal Cord. Mar 1997;35(3):147-150. 37. Ravaud JF, Delcey M, Desert JF. The Tetrafigap Survey on the long-term outcome of tetraplegic spinal cord injured persons, part II: Demographic characteristics and initial cause of injury. Spinal Cord. Mar 2000;38(3):164-172. 38. Shingu H, Ikata T, Katoh S, Akatsu T. Spinal cord injuries in Japan: a nationwide epidemiological survey in 1990. Paraplegia. Jan 1994;32(1):3-8. 39. Masood Z, Wardug GM, J A. Spinal Injuries: Experience of a local neurosurgical centre. Pak J Med Sci 2008;24(3):368-371. 40. Levy LF, Makarawo S, Madzivire D, Bhebhe E, Verbeek N, Parry O. Problems, struggles and some success with spinal cord injury in Zimbabwe. Spinal Cord. Mar 1998;36(3):213-218. 41. Tooth L, McKenna K, Geraghty T. Rehabilitation outcomes in traumatic spinal cord injury in Australia: functional status, length of stay and discharge setting. Spinal Cord. Apr 2003;41(4):220-230. 42. Center NSCIS. 2006 NSCISC Annual Statistical Report. http://images.main.uab.edu/spinalcord/pdffiles/NSCIC%20Annual%2006.pdf. Accessed December 30. 43. Karamehmetoglu SS, Nas K, Karacan I, et al. Traumatic spinal cord injuries in southeast Turkey: an epidemiological study. Spinal Cord. Aug 1997;35(8):531-533. 44. Ahoniemi E, Alaranta H, Hokkinen EM, Valtonen K, Kautiainen H. Incidence of traumatic spinal cord injuries in Finland over a 30-year period. Spinal Cord. Dec 2008;46(12):781-784. 45. Jackson AB, Dijkers M, Devivo MJ, Poczatek RB. A demographic profile of new traumatic spinal cord injuries: change and stability over 30 years. Arch Phys Med Rehabil. Nov 2004;85(11):1740-1748. 46. Nobunaga AI, Go BK, Karunas RB. Recent demographic and injury trends in people served by the Model Spinal Cord Injury Care Systems. Arch Phys Med Rehabil. Nov 1999;80(11):1372-1382. 47. O'Connor PJ. Forecasting of spinal cord injury annual case numbers in Australia. Arch Phys Med Rehabil. Jan 2005;86(1):48-51. 48. Pagliacci MC, Celani MG, Zampolini M, et al. An Italian survey of traumatic spinal cord injury. The Gruppo Italiano Studio Epidemiologico Mielolesioni study. Arch Phys Med Rehabil. Sep 2003;84(9):1266-1275. 49. Hart C, Williams E. Epidemiology of spinal cord injuries: a reflection of changes in South African society. Paraplegia. Nov 1994;32(11):709-714. 50. Maynard FM, Jr., Bracken MB, Creasey G, et al. International Standards for Neurological and Functional Classification of Spinal Cord Injury. American Spinal Injury Association. Spinal Cord. May 1997;35(5):266-274. 51. Dryden DM, Saunders LD, Jacobs P, et al. Direct health care costs after traumatic spinal cord injury. J Trauma. Aug 2005;59(2):443-449. 52. Catz A, Thaleisnik M, Fishel B, et al. Survival following spinal cord injury in Israel. Spinal Cord. Nov 2002;40(11):595-598. 53. Paker N, Soy D, Kesiktas N, et al. Reasons for rehospitalization in patients with spinal cord injury: 5 years' experience. Int J Rehabil Res. Mar 2006;29(1):71-76. 54. Rathore MF, Hanif S, Farooq F, Ahmad N, Mansoor SN. Traumatic spinal cord injuries at a tertiary care rehabilitation institute in Pakistan. J Pak Med Assoc. Feb 2008;58(2):53-57. 55. O'Connor PJ. Trends in spinal cord injury. Accid Anal Prev. Jan 2006;38(1):71-77. 56. Chen CF, Lien IN. Spinal cord injuries in Taipei, Taiwan, 1978-1981. Paraplegia. Dec 1985;23(6):364-370. 57.李燕鳴.急診醫療中檢驗事故傷患之血中酒精濃度的相關因素.台灣家醫誌 2003;13:109-19 58.李燕鳴.花蓮縣風險性駕駛肇事之交通事故分析.慈濟醫學雜誌 2003;15:175-83 59. Kraus JF. Injury to the head and spinal cord. The epidemiological relevance of the medical literature published from 1960 to 1978.J Neurosury 1980; 53 (Suppl):S3-10. 60. Lan C, Lai JS, Chang KH, Jean YC, Lien IN. Traumatic spinal cord injuries in the rural region of Taiwan: an epidemiological study in Hualien country, 1986-1990. Paraplegia 1993; 31: 398-403. 61.林樹基,林茂榮,蔡卓城,蔡行瀚,江富偉,李蔚貞, 邱文達 台北市交通事故和跌落導致急性脊椎傷害病人的特質比較 J Emerg Crit Care Med. 2009; 20:183-194 62.陳姿怡,陳瑞杰,盧立華,蔣永孝,方禎鋒,李孟如,林茂榮 創傷性脊髓損傷者一年 內存活及影響因子 FJPT 2006;31(2):87-97 碩士 指導教授-邱文達 委員-白璐 委員-蔣明富 目的：針對創傷性脊髓損傷患者其基本資料及受傷經過作描述性的統 計分析，並深入探討相關危險因子與損傷嚴重度的差異性及預 後結果的相關性 方法：本研究之研究對象是來自「中華民國頭脊髓外傷研究小組」所 收集之創傷性脊髓損傷資料庫，此資料庫包含合作醫院中花蓮 縣4家與台北市20家區域級以上中大型醫院之創傷性脊髓損傷 病患，合計共976人。資料以SPSS15版套裝軟體整合相關資 料進行分析，類別變項資料使用卡方檢定(Chi-Square)檢驗，另外也使用邏輯式迴歸分析來檢測危險因子與受傷嚴重度的相關性。以P值小於0.05為顯著差異的標準。 結果：近二年創傷性脊髓損傷患者有稍減，平均受傷年齡49.31歲，男女性比為2:1，受傷原因皆以車禍為主，受傷部位以頸椎最多占68.3%，脊髓神經障礙種類以四肢不完全癱居多25.1%，合併傷害部位以頭部外傷占70.9%，加護病房平均住院天數5.6天，受傷結果死亡8.3%、神經障礙種類造成之受傷結果以無行動障礙且能獨立居多57.2%，進一步以受傷結果(死亡及植物人)與脊髓神經障礙種類作分析以其他脊髓神經障礙作為參考族群，四肢全癱的患者較為死亡與植物人的風險為參考族群0.78倍，達統計學上顯著差異(95%CI:1.04-90.01)。 結論：創傷性脊髓損傷其所衍生的神經學後遺症及殘障，會對傷者本身及其家庭造成相當大的生活負擔，而長期醫療照護與復健的開銷，更是龐大的社會經濟負擔，也威脅整個國家的經濟發展力，因此要降低創傷性脊髓損傷的發生率與死亡率，必須針對相關危險因子進行介入措施，如降低行車超速與酒後駕車的行為，預防老人跌落所造成的傷害，同時也要加強緊急醫療救護及復健醫療照護，因其照護品質的優劣會影響到傷者的存活與預後情形的重要因素，使脊髓損傷患者能獲得及時與適當的醫療照護以延長壽命，並降低社會醫療成本。 Goals: To provide descriptive characteristics and history of the traumatic events for patients with traumatic spinal cord injuries. This study further examined the associations between risk factors and severity and prognosis of the injuries. Methods: Study subjects included 976 patients with traumatic spinal cord injuries in the Taiwan National Head Injury Database collected (time period?) by the Head and Spinal Injury Research Team. This Database collected data from 4 hospitals in Hualien County and 20 regional hospitals in Taipei City in Taiwan. Chi-square statistics and logistic regressions were used. All analyses were conducted using statistic software SPSS15 with a significance level of 0.05. Results: There was a decrease in incidence of traumatic spinal cord injuries in the past two years. The average age of patients was 49.31 years. Males were twice more likely than females to encounter the injuries. The main cause of the injuries was automobile accidents. About 68.3% of the injuries occurred in neck spinal cord. Partial paralysis of four limbs was among the most prevalent injuries, accounting for more than one quarter (25.1%). Most (70.9%) of injuries occurred in head. The average length of stay in intensive care units was 5.6 days. About 8.3% of the patients died. More than half (57.2%) recovered with no limitations in movement and were able to live independently. Compared to those with other spinal cord injuries, patients with complete paralysis of four limbs were statistically significantly 0.78 times more likely to die or in vegetable status (95%CI1.04-90.01). Conclusions: The impacts of traumatic spinal cord injuries not only impose tremendous burdens for the patients and their families, but also for the society as a whole. Therefore, the study of traumatic spinal cord injuries was among the top priority worldwide. To reduce the incidence and mortality of the traumatic spinal cord injuries, it is warranted to focus interventions on the risk factors. Examples include decrease in speeding or driving under influence and fall prevention for the elderly. Furthermore, it is necessary to strengthen the emergency medical care and rehabilitation care systems, which play significant roles in the survival and prognosis of patients as well as the improvement of nationwide traumatic spinal cord care system. As a result, patients with traumatic spinal cord injuries may receive timely and adequate care, prolong their lives. The country may reduce the medical care costs.